INVESTIGATING THE RELATIONSHIP BETWEEN MENTAL RETARDATION AND LEAD INTOXICATION - Boran, Ahmad M; Al-Bashir, Nabil A; Al-Khatib, Ahed J; Qattan, Ilham T; Alanazi, Saud A; Massadeh, Adnan M (European Scientific Journal, ESJ, 2013)
Introduction: There has been a debate in literature to correlate lead (Pb) poisoning with mental retardation since lead can be involved in developmental stage and induce brain damage; in particular, children under age of 10 years. Study objectives: To determine blood Pb levels among mentally retarded patients at Jerash Center for Welfare and Rehabilitation and to correlate clinical study variables with blood Pb levels. Methodology: Study design and setting: Cross-sectional experimental study design. The present study was conducted at Jerash Center for Welfare and Rehabilitation. A convenient sample of 90 participants was included in the present study. Blood Pb level was analyzed at Princess Haya Center for Biotechnology using Atomic Absorption Spectrometry. Results: The( mean ± Sd) concentration of Pb is 0.6 ± 2.7 μg/dl. There was a significant relationship between age and blood Pb level (p value < 0.001). The results showed that more blood Pb concentrations were associated with mental retardation and physical impairment. More blood Pb levels were detected among mental retardation cases in irbid. Conclusion: Although most cases of mental retardation were associated with undetectable blood Pb levels, it is still important to take into account the possibility of involvement of lead among mentally retarded patients. Recommendations: 1- In the present study, 90 cases out of 230 resident cases in Jerash Center for Welfare and Rehabilitations were included in the study for Pb analysis. It is recommended to carry out the analysis of blood for the all cases. 2- It is also recommended to carry out analysis for other heavy metals such as chromium for patients. 3- To adopt policies and measures to decrease the exposure of children to Pb and other toxic heavy metals. Measures include removing of paint chips from houses and controlling the behavior of children to inhibit ingestion of things with potential content of heavy metals through hand to mouth behavior such as soil (controlling pica behavior).